Teologi Hospitalitas: Sebuah Diskursus Konstruktif Agama Merevitalisasi Nilai-nilai Kemanusiaan - Siahaan, Harls Evan R; Kause, Munatar; Siagian, Fereddy (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2022)
The sense of humanity has been disrupted by issues that have led to conflict and violence in the name of religion. Religious identity is often used as a barrier that sharply distinguishes adherents of one religion from another so that the identity differences put each as